PENGARUH ESG (ENVIRONMENTAL SOCIAL GOVERNANCE), PERTUMBUHAN ASSET, DAN SIKLUS HIDUP PERUSAHAAN TERHADAP CASH HOLDING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2020-2022 - Widia Yuliana; Ahmad Sumarlan; Hernadianto Hernadianto; Nensi Yuniarti Zs (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the influence of ESG (Environmental Social Governance), asset growth, and company life cycle on cash holdings in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2022 period. The research method used is a quantitative method using secondary data obtained from annual reports and sustainability reports of manufacturing companies listed on the IDX. The study population consisted of 209 companies, with a research sample of 48 observations selected using a purposive sampling technique. Data analysis was performed using multiple linear regression with the help of the SPSS program. The results showed that ESG had a negative and significant effect on cash holdings with a significance value of 0.007 and a regression coefficient of -0.203, asset growth had a negative and significant effect on cash holdings with a significance value of 0.001 and a regression coefficient of -0.119, and company life cycle had a negative and significant effect on cash holdings with a significance value of 0.004 and a regression coefficient of -0.098. Simultaneously, ESG, asset growth, and the company's life cycle significantly influence cash holdings, with a significance value of 0.000 and an Adjusted R Square of 0.322. The conclusion of this study indicates that increased ESG disclosure, asset growth, and the development of the company's life cycle tend to reduce the level of cash holdings in manufacturing companies due to the increasing need for funds for operational activities, investments, and corporate responsibilities. These three variables are able to explain 32.2% of the variation in cash holdings, while the remainder is influenced by other factors outside the study. Keywords: ESG (Environmental Social Governance), Asset Growth, Company Life Cycle, Cash Holding, Manufacturing Companies